Ethnic Diversity in Teaching Sorogan of Pesantren - Karimah, Ummah (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2018)
This study aims to describe the teaching of sorogan in the pursuit of books in Pesantren (Islamic boarding schools) with ethnic diversity. Ethnic diversity of the kyai (teacher) and the santri (student). This research explains the implementation of sorogan teaching to produce a product in santri. This research is descriptive qualitative research. In collecting data used the interview method and observation. The results of this study are that in the learning process using the Sorogan method there are problems in the adjustment of santri in taking lessons and the cultural language of the pesantren itself as a learning process of the santri in Islamic boarding schools.